(untitled) (Research, Society and Development, 2021)
The ordinance No. 648 of 2006 approves the National Policy for Primary Care, which, among other deliberations, defines actions in health education and professional qualification, in order to meet this perspective, the Education through Work for Health Program emerged. This study is an experience report of experiences in the PET-SAÚDE/GRADUASUS 2016/2017 Program, aimed at developing teaching, research and extension activities aimed at working in a Basic Family Health Unit. We had the opportunity to articulate and articulate knowledge from various areas, create documents and flowcharts that will make the diagnosis and management of Hypertension made earlier and more effectively, promoting the strengthening and attention to the person through comprehensiveness and of the longitudinality of care, at all points of care. This data collection reinforces the development of the lines of care for SAH, and the PET-SAÚDE/GRADUASUS, by joining forces with the graduation, allows for a broader reading of the complex process in which chronic degenerative diseases present themselves, enabling the expansion of knowledge, and enables learning focused on the reality of the SUS, increases the criticality and the ability to act and solve problems, which is of great value for the improvement of professional skills.